Optimalisasi Penggunaan Obat yang Rasional: Implementasi DAGUSIBU - Yulius Evan Christian; Sherly Tandi Arrang (CARADDE: Jurnal Pengabdian Kepada Masyarakat, 2025)
Abstract.Improper medication management can lead to health risks, such as overdoses, side effects, and environmental pollution. The educational program on obtaining, storing, and disposing of medication aims to enhance public understanding of safe, effective, and responsible practices. This program is crucial as many people lack knowledge about legally obtaining medications, using them correctly, storing them to maintain quality, and disposing of them safely. The activity involved 44 participants, predominantly women over 45 years, with most having low educational backgrounds. Methods included lectures, practical simulations, group discussions, and evaluations through pretest and posttest. The results demonstrated a significant improvement in participants' knowledge. Before the program, only 15.91 percent of participants were in the good category, increasing to 38.64 percent after the program. Those with sufficient knowledge also increased, while the poor category decreased from 27.27 percent to 18.18 percent. In conclusion, the program significantly enhanced participants' knowledge, showing that lecture and practical simulation methods significantly improved public health literacy